GHG mitigation efforts on dairy farms in the Netherlands: From objectives to best practices and implementation - Zijlstra, Jelle; Vellinga, Theun V. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
This presentation was given by Jelle Zijlstra and Theun Vellinga at the kick-off meeting on "Piloting and scaling of low emission development options in large scale dairy farms in China" on September 28, 2020.